A Comprehensive Review and Analysis of Intestinal Parasitic Infections in School Children from South India - Vinay Khanna; Suhas Alur; Ruchee Khanna; Seemitr Verma (Archives of Medicine and Health Sciences)
Background and Aim: According to the World Health Organization, close to 21% of India’s population may be affected by intestinal parasites, accounting for 39 million disability-adjusted life years, which may likely be due to substandard sanitation practices and insufficient personal hygiene standards. This research was conducted with the aim of determining the prevalence of helminthic infections among school-aged children in the South Canara district of India. Materials and Methods: We conducted a cross-sectional study involving school children from nursery to the 8th Grade in the South Canara district of Karnataka, India. The presence of various intestinal parasites in different age groups was determined by performing routine stool microscopy. Modified acid-fast staining was performed for stool samples collected from children <5 years of age for the detection of intestinal coccidian parasites. Statistical analysis was carried out to analyze age-related trends in relation to the prevalence of commonly detected intestinal parasites. Results: Intestinal parasites were identified in 10 of the 253 students (3.9%), with the highest incidence observed in the age group of 7–10 years (1.9%). The most prevalent parasite identified was the cysts of Giardia lamblia, with a prevalence of 7.54%, followed by Ascaris lumbricoides and hookworm, each having a prevalence of 5.66%. Of the 253 students, 92.2% practiced handwashing with soap after defecation, while 7.8% did not use soap. The handwashing practices did not significantly vary across different age groups. Clinically, pallor was observed in 64.2% of the individuals. Conclusion: Giardiasis was the most common parasitic infection, followed by soil-transmitted helminths such as Ascariasis and hookworm. The level of hygiene practices among children exceeded the prevailing national and state standards.